Roberto Burgio: the scientist at the service of every new life born into the world [Article in English and Italian] • [Roberto Burgio: lo scienziato al servizio di ogni nuova vita nata al mondo] [Article in English and Italian] - Italo Farnetani; Francesca Farnetani (Hygeia Press di Corridori Marinella, 2014)
Burgio was a great master of pediatrics; he surely contributed to the progress of medicine and science in general. "Nobody is born of his own will and therefore we are all committed to ensuring that those who are born live good lives. Parents first of all, but obviously pediatricians at their sides. This is a maxim that I have placed on the back cover of the 5th edition of Pediatria Essenziale", he said during the presentation of his book in Pavia. Pediatria essenziale is the text of pediatrics which, from its 1stedition in 1978, has been a book studied and consulted by students, physicians and pediatricians and which guided Roberto Burgio's thought up to the final edition in 2012 to which he applied some five years of total commitment, with the involvement of 120collaborators, a number so large that he defined it a "choral" work. He reviewed and verified every page in contact with the authors to whom he sent questions and requests for extensions. It was thus "his book", the one to which he entrusted his thought, his knowledge, his being a man and physician. It is thus a work that will remain in the annals of pediatrics.   [Burgio è stato un grande maestro di pediatria, e sicuramente ha contribuito ai progressi della medicina e della scienza in generale. "Nessuno nasce per propria volontà e, quindi, siamo tutti impegnati a far vivere bene chi nasce. Genitori in primo luogo; ma Pediatri ovviamente, con essi. È una mia massima che ho riportato in IV di copertina di Pediatria Essenziale, V edizione", affermò durante la presentazione del suo libro a Pavia. La Pediatria essenziale è il testo di pediatria che, dalla I edizione del 1978, è stato un libro studiato e consultato da studenti, medici e pediatri e che ha veicolato il pensiero di Roberto Burgio, fino all'ultima edizione del 2012 alla quale ha dedicato circa cinque anni di dedizione assoluta, coinvolgendo 120 collaboratori, tanto che la definì un'opera "corale". Ha riguardato e verificato ogni pagina, confrontandosi con gli autori, ai quali ha spedito quesiti e richieste di ampliamento. È stato perciò il "suo libro" quello a cui ha affidato il suo pensiero, il suo sapere, il suo essere uomo e medico. È pertanto un'opera che resterà nella storia della pediatria.]